1993
DOI: 10.1084/jem.177.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific alterations in the B oligomer that affect receptor-binding activities and mitogenicity of pertussis toxin.

Abstract: SummaryPertussis toxin plays a major role in the pathogenesis of whooping cough and is considered an important constituent of vaccines against this disease. It is composed of five different subunits associated in a molar ratio 1S1:1S2:1S3:2S4:1S5. The $1 subunit is responsible for the ADPribosyltransferase activity of the toxin. The B moiety, composed of $2 through $5, recognizes and binds to the target cell receptors and has some ADP-ribosyltransferase-independent activities such as mitogenicity. Site-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The C-terminal half of S2 and of S3 adopt a fold similar to that found in the B subunits of other carbohydrate-binding toxins, and the sialyl group of the oligosaccharide bound to PTX is within hydrogen-bonding distance of the polar and charged groups of Tyr-102, Ser-104, and Arg-125 in both S2 and S3 [44,45]. Site-specific alterations of the residues in that region abolish receptor binding of PTX [45,46]. Interestingly, deletion of Asn-105 in S2 affects haptoglobin binding of the toxin, while keeping its ability to bind to CHO cells intact, whereas the deletion of Lys-105 in S3 has the inverse effect [45], indicating that these residues contribute to receptor-binding specificity.…”
Section: Molecular Mechanisms Of Ptx Actionmentioning
confidence: 96%
See 3 more Smart Citations
“…The C-terminal half of S2 and of S3 adopt a fold similar to that found in the B subunits of other carbohydrate-binding toxins, and the sialyl group of the oligosaccharide bound to PTX is within hydrogen-bonding distance of the polar and charged groups of Tyr-102, Ser-104, and Arg-125 in both S2 and S3 [44,45]. Site-specific alterations of the residues in that region abolish receptor binding of PTX [45,46]. Interestingly, deletion of Asn-105 in S2 affects haptoglobin binding of the toxin, while keeping its ability to bind to CHO cells intact, whereas the deletion of Lys-105 in S3 has the inverse effect [45], indicating that these residues contribute to receptor-binding specificity.…”
Section: Molecular Mechanisms Of Ptx Actionmentioning
confidence: 96%
“…Site-specific alterations of the residues in that region abolish receptor binding of PTX [45,46]. Interestingly, deletion of Asn-105 in S2 affects haptoglobin binding of the toxin, while keeping its ability to bind to CHO cells intact, whereas the deletion of Lys-105 in S3 has the inverse effect [45], indicating that these residues contribute to receptor-binding specificity. Other regions, in particular in the N-terminal domain of these subunits, may also be involved in receptor recognition [47].…”
Section: Molecular Mechanisms Of Ptx Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure of PTX bound to a undecasaccharide revealed at least two carbohydrate-binding sites on the S2 and S3 subunits, respectively (Figure 1) [50]. However, the two binding sites display a certain degree of receptor-binding specificities [51]. Surface plasmon resonance studies using carbohydrate ligands showed that binding to sialylated compounds is mediated by the C-terminal binding sites on the S2 and S3 subunits, while binding to nonsialylated N-linked glycans is mediated by their N-terminal sites [52].…”
Section: Toxin Binding Trafficking and Enzymatic Activities On The Hosmentioning
confidence: 97%